PEMBELAJARAN SENI DI MASYARAKAT - Sudartomo Macaryus (Universitas Sanata Dharma, 2008)
Art is one of the universal cultural elements. Therefore, every cultural social community has a certain kind of art. The strategy of art learning can be carried out through three steps: invite the children to know, enjoy, and practice it. Art learning in the society endures longer, because the society keeps living, growing, and developing. The loyalty of the guide, the members, the target to performance, never reject a new member, and optimally the society commitment. Another strategy is making a collaboration with three educational centers, i.e. Family, society, and school. The collaboration can take the form of a member recruitment, guide, the use major and minor facilities, and the target of performance. The role of the government in learning art is to give a space, be a data and information center, document center, mediator to link the art groups with institutions in need, give an honor to those curative and outstanding, supply publication, and encouragement.KEY WORDS art, learning, loyalty, participation, three centers of education